Preparation, Characterization, and Oxygenase Activity of a Photocatalytic Artificial Enzyme - Gu, Yifan (Chembiochem, 2015)
A bicyclo[6,1,0]nonyne-substituted 9-mesityl-10-methyl-acridinium cofactor was prepared and covalently linked to a prolyl oligopeptidase scaffold containing a genetically encoded 4-azido-L-phenylalanine residue in its active site. The resulting artificial enzyme catalyzed sulfoxidation when irradiated with visible light in the presence of air. This reaction proceeds via initial electron abstraction from the sulfide within the enzyme active site, and the protein scaffold extended the fluorescence lifetime of the acridium cofactor. The mode of sulfide activation and placement of 5 in POP-ZA(4)-5 make this artificial enzyme a promising platform for developing selective photocatalytic transformations.